Does commonality in illiquidity matter to investors? - Richard G. Anderson; Jane M. Binner; Björn Hagströmer; Birger Nilsson (University of Birmingham, Birmingham Business School, 2015)
This paper investigates whether investors are compensated for taking on commonality risk in equity portfolios. A large literature documents the existence and the causes of commonality in illiquidity, but the implications for investors are less well understood. In a more than fifty year long sample of NYSE stocks, we find that commonality risk carries a return premium of around 2.6 per cent annually. The commonality risk premium is statistically and economically significant, and substantially higher than what is found in previous studies. It is robust when controlling for illiquidity level effects, different investment horizons, as well as variations in illiquidity measurement and systematic illiquidity estimation.
Keywords: 330